NILAI-NILAI PENDIDIKAN KARAKTER DALAM PEMBELAJARAN KITAB BALAGHAH DI PESANTREN: LITERATURE REVIEW - Mahfudz Syamsul Hadi; Abdul Muhid (Risalah, Jurnal Pendidikan dan Studi Islam, 2022)
The book of Al-Jauharul Maknun is a masterpiece of a scholar' alim al-'allamah Sheikh Abdurrahman Al-Ahdlori which contains the faidah-faidah and qoidah-qoidah of Balaghoh science. This book is hundreds of years old and is used by academics, students, and madrasa students, both at home and abroad. Only a small number of students parse and examine books from different angles. In fact, this book is full of useful information. Likewise, it is very important to reveal the essence of the moral ideals of the balaghoh book. This publication aims to clarify the content of moral principles, internalization procedures, and reflection on the impact of moral internalization for santri in Islamic boarding schools.